First Solar Orbiter observation of the Alfvenic slow wind and identification of its solar source - D'Amicis,R; Bruno,R; Panasenco,O; Telloni,D; Perrone,D; Marcucci,MF; Woodham,L; Velli,M; De,Marco R; Jagarlamudi,V; Coco,I; Owen,C; et al. (Astronomy and Astrophysics: a European journal, 2021)
Context. Turbulence dominated by large-amplitude, nonlinear Alfvén-like fluctuations mainly propagating away from the Sun is ubiquitous in high-speed solar wind streams. Recent studies have demontrated that slow wind streams may also show strong Alfvénic signatures, especially in the inner heliosphere.Aims. The present study focuses on the characterisation of an Alfvénic slow solar wind interval observed by Solar Orbiter between 14 and 18 July 2020 at a heliocentric distance of 0.64 AU.Methods. Our analysis is based on plasma moments and magnetic field measurements from the Solar Wind Analyser (SWA) and Magnetometer (MAG) instruments, respectively. We compared the behaviour of different parameters to characterise the stream in terms of the Alfvénic content and magnetic properties. We also performed a spectral analysis to highlight spectral features and waves signature using power spectral density and magnetic helicity spectrograms, respectively. Moreover, we reconstruct the Solar Orbiter magnetic connectivity to the solar sources both via a ballistic and a potential field source surface (PFSS) model.Results. The Alfvénic slow wind stream described in this paper resembles, in many respects, a fast wind stream. Indeed, at large scales, the time series of the speed profile shows a compression region, a main portion of the stream, and a rarefaction region, characterised by different features. Moreover, before the rarefaction region, we pinpoint several structures at different scales recalling the spaghetti-like flux-tube texture of the interplanetary magnetic field. Finally, we identify the connections between Solar Orbiter in situ measurements, tracing them down to coronal streamer and pseudostreamer configurations.Conclusions. The characterisation of the Alfvénic slow wind stream observed by Solar Orbiter and the identification of its solar source are extremely important aspects for improving the understanding of future observ